Інтернаціоналізація інституційного освітнього простору Великої Британії - Чернякова, Жанна (Studies in Comparative Education, 2014)
У статті проаналізовано й розкрито стратегії інтернаціоналізації інституційного освітнього простору; виокремлено та схарактеризовано міжнародну стратегію інтернаціоналізації на рівні навчального закладу. Визначено і здійснено аналіз програмної та організаційної стратегій інтернаціоналізації інституційного освітнього простору; з’ясовано ключові компоненти та встановлено пріоритетні напрями зазначених стратегій; розкрито завдання інтернаціоналізації інституційного освітнього простору в контексті визначених стратегій. В статье проанализированы и раскрыты стратегии интернационализации институционального образовательного пространства; выделена и охарактеризована международная стратегия интернационализации на уровне учебного заведения. Определены и осуществлен анализ программной и организационной стратегий интернационализации институционального образовательного пространства; выяснено ключевые компоненты и установлено приоритетные направления указанных стратегий; определены задачи интернационализации институционального образовательного пространства в контексте установленных стратегий. The author of the article explores and reveals the strategy of internationalization of institutional education space in Great Britain. It is emphasized that the internationalization of education as a key vector of the formation of modern education policy in Europe and the world. Current understanding of the internationalization represents it as the process of integrating an international dimension into teaching and learning, research and social services of institution, in developing strategies of education, aimed at forming global thinking of young people from the perspectives of modern society. In the context of our study, we note that the internationalization of the educational institution space is defined by the international strategy at the institutional level. Internal and external factors of international strategy at the institutional level are presented in the work of the researcher G. Keller. The article defines and analyzes the programme and organizational strategies of internationalization of institutional education space. Detailed and comprehensive analysis of the strategies of internationalization of institutional education space are presented in the works of J. Knight and H. de Wit. Considering activity the key component of the internationalization of educational space, scientists distinguish two main strategies: the programme (academic activities and educational services of institution that focuse on implementing the international dimension) and organizational (international educational policy of the institution administration). The key components and priorities of mentioned above strategies have been found. The priorities of the program strategy of internationalization of education are considered: academic programs, research cooperation, technical assistance, external relations, services (domestic and abroad), extracurricular activity. The key components of the organizational strategy of internationalization of institutional education space, according to scientist J. Knight, are administrative management, educational activities, support, development potential subjects of the educational process. In the context of the study the priorities of internationalization of institutional educational space are clarified, namely the convergence of national educational systems through international education policy, international organizational structure, content, forms and methods of training, single system requirements for graduates and students, international cooperation, and the only mechanism methods for assessing the quality of education (accreditation, educational programs that meet international standards), the system of monitoring the quality of education and participation in international monitoring studies, the development of research in the field of education, taking into account world trends in education approximation of legislative and regulatory framework in education and science, their compliance with international standards.